Geometric functions of stress intensity factor solutions for spot welds in coach-peel specimens. (May 2016) - Lin, Z.-L.; Lin, P.-C.
Highlights: Geometric effects on stress intensity factors of coach-peel specimens are studied. 3D FE models are developed to obtain accurate stress intensity factor solutions. Effects of various geometric parameters on geometric factors are studied by FEA. Appropriate specimen dimensions and corresponding geometric factors are suggested. Abstract: Stress intensity factor solutions for spot welds in two kinds of coach-peel specimens are investigated by finite element analyses. Three-dimensional finite element models are developed to obtain accurate solutions. Various ratios of sheet thickness, specimen width, flange length, and effective wall height to nugget radius are considered. The results confirm the functional dependence on the nugget radius and sheet thickness of Zhang's analytical solution. Two geometric functions in terms of the normalized geometric parameters for Zhang's solution are obtained. Based on the analytical and computational results, the dimensions of coach-peel specimens and the corresponding approximate stress intensity factor solutions are suggested.